Compliance Properties of Collagen-coated Polyethylene Terephthalate Vascular Prostheses. Issue 3 (September 2014) - Khoffi, Foued; Mathieu, Daniel; Dieval, Florence; Chakfé, Nabil; Durand, Bernard
Background: Compliance mismatch between native artery and a prosthetic graft used for infrainguinal bypass is said to be a factor for graft failure. The aim of this study was to develop a technique for measuring the compliance of collagen-coated polyethylene terephthalate (PET) vascular prostheses and to analyze the influence of several key properties on the elastic behavior of the grafts. Methods: Compliance testing was performed on 3 prostheses with and without internal compliant membrane (ICM). The principle of this test was to study the dimensional changes of prostheses submitted to internal pressure from 30 to 240 mm Hg at intervals of predetermined values. Results: We demonstrated that the ICM created links with the inner surface of the crimps and considerably modified the graft behavior when submitted to internal pressure. The results showed that compliance properties were dependent on the wall thickness and the crimping geometry of textile vascular prostheses. Mechanical analysis predicts the circumferential tensile behavior of these arterial grafts and validates tests for measuring compliance.